Photic hypersensitivity in the premonitory phase of migraine – a positron emission tomography study. (30th April 2014) - Maniyar, F. H.; Sprenger, T.; Schankin, C.; Goadsby, P. J.
<x xml:space="preserve">Abstract</x> Background and purpose Sensitivity to light (photophobia) is a common ill‐understood symptom of migraine, whose neurobiology is important in understanding the disorder. Methods Patients reporting premonitory symptoms before migraine headache were infused with nitroglycerin (GTN) at a first visit. Patients who responded with premonitory symptoms followed by a delayed headache resembling their migraine had positron emission tomography (PET) scans at least 1 week later, during which GTN infusion was repeated. H215O PET scans were performed during baseline (pain free), premonitory phase (pain free) and migraine headache. Patients were divided into two groups, with and without photophobia in the premonitory phase. The differences between the premonitory and baseline scans were analysed within groups and between groups using statistical parametric mapping. Results Thirteen patients participated in the PET study, 10 of whom had at least one PET scan during the premonitory phase in the absence of pain. Data from these 10 patients were included in the final analysis. Five patients had photophobia and five patients did not have photophobia in the premonitory phase. Comparing the premonitory scans to baseline scans, there was activation of extrastriate visual cortex (BA18) in patients with photophobia. This activation was significantly greater than in the patients without photophobia. Conclusion Our findings indicate that photic hypersensitivity is linked to activation of the visual cortex during the premonitory phase of migraine in the absence of headache.